Calorific Values of PETRONAS Cokes Nitrated at Various Temperatures - Mohd.Shaiful Baharuddin bin Halim, Mohd.Shaiful Baharuddin (Universiti Teknologi Petronas, 2010)
Petroleum coke (Petcoke) is the petroleum refining byproduct in the form of solid. It is useful in the manufacturing of electrodes used as carbon anodes for the aluminum industry, graphite electrodes for steel making, as fuel in the firing of solid fuel boilers used to generate electricity, and as fuel for cement kilns. Malaysia is one of the countries that produce a very high percentage of all petcoke, and coking capacity continues to increase. Petcoke is very important because of increasing cement industry and growing of usage within the electricity generating and industrial boiler communities as well.